Karakteristik Fenotipik dan Pengelompokan Jagung Pulut Hibrida Zea mays L. Hasil Persilangan Puncak - Juhriah Juhriah; Muhammad Azrai; Elis Tambaru; Jum Eka Rahayu (Jurnal Ilmu Alam dan Lingkungan, 2019)
This research is the phenotypic characteristics and grouping of hybrid waxy corn Zea mays L. product of the top cross had been carried out in the experimental plant Indonesian Cereals Research Institute (ICERI) in Maros South Sulawesi. This research aims to determine the phenotypic characters of the hybrid of waxy corn Zea mays L. product of the top cross and grouping based on its phenotypic characteristics. This research used a randomized block design (RBD) with 17 th treatments (corn strains) and three replications. Waxy corn strains used were: URI 1 (G8), G8G1, G8G2, G8G3, G8G4, G8G5, G8G6, G8G7, Soppeng (G10), G10G1, G10G2, G10G3, G10G4, G10G5, G10G6, G10G7, and Paramitha.. All data (qualitative and quantitative) are arranged in binary tables and grouped using the NTSYST program. The observations show that the data obtained comes from 14 quantitative characters and 17 qualitative characters. Quantitative data from 14 characters were tested and the results of 10 characters were significantly different and the other 4 were not significantly different. The grouping results show that the 17 corn strains studied formed 3 groups at the similarity coefficient of 0.76. Soppeng's corn is different from the others.